Molecular characterization and expression of TGFβRI and TGFβRII and its association with litter size in Tibetan sheep. Issue 2 (7th January 2023) - Zhang, Junxia; Li, Mingming; Sun, Ruizhe; He, Na; Wen, Xiaocheng; Han, Xueping; Luo, Zenghai
Abstract: Backgrounds: Transforming growth factor‐β (TGF‐β) type I receptor (TGFβRI) and type II receptor (TGFβRII) are the members of the TGFβ superfamily, which are potent regulators of cell proliferation and differentiation in many organ systems, and they play key roles in multiple aspects of follicle development. Objectives: We aimed to explore the characterization, expression analysis of TGFβRI and TGFβRII genes, and the association with litter size in Tibetan sheep. Methods: In this study, we cloned the complete coding sequences of TGFβRI and TGFβRII genes in Tibetan sheep and analyzed their genomic structures. Results: The results showed that percentages of sequences homology of the two proteins in Tibetan sheep were the most similar to Ovis aries (100%), followed by Bos mutus (99%). The RT‐qPCR showed that two genes were expressed widely in the different tissues of Tibetan sheep. The TGFβRI expression was the highest in the lung ( p < 0.05), followed by the spleen and ovary ( p < 0.05). The TGFβRII expression was significantly higher in uterus than that in lung and ovary ( p < 0.05). In addition, the χ 2 test indicated that all ewes in the population were in Hardy–Weinberg equilibrium, and the population was in medium or low polymorphic information content status. We also found four Single Nucleotide Polymorphism (SNPs), g.9414A > G, g.28881A > G, g.28809T > C, g.10429G > A in sheep TGFβRI gene and g.63940C > T, g.63976C > T, g.64538C > T, g.64504T > A in TGFβRII gene. Three genotypes, except for g.64504T > A, and three haplotypes were identified in each gene. linkage disequilibrium analysis indicated that there was strong linkage disequilibrium in each gene. The association analysis showed that the four SNPs of TGFβRI were associated with litter size ( p < 0.05), and g.63940C > T of TGFβR II was confirmed to be associated with litter size ( p < 0.05). Conclusions: Based on these preliminary results, we can assume that TGFβ receptors (TGFβRI and TGFβRII) may play an important role in sheep reproduction. Abstract : This study was undertaken to explore the characterization, expression analysis of TGFβR I and TGFβR II genes, and its association with litter size in Tibetan sheep. The TGFβ receptors (TGFβRI and TGFβR II) may play an important role in sheep reproduction.